2017
DOI: 10.11648/j.ijmsa.20170601.16
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Synthesis of Silica Powder from Rice Husk Ash as Reinforcement Filler in Rubber Tire Tread Part: Replacement of Commercial Precipitated Silica

Abstract: Abstract:Rice husks, which can be considered as an agricultural waste, are produced every year in South Gonder, Ethiopia.Precipitated silica is commonly used as reinforcing filler in rubber industry, in the present study an effort has been attempted to replace commercial silica commonly used in natural rubber industries with rice husk ash silica (RHAS). Silica was extracted from RHA by using alkaline extraction followed by acid precipitation. The synthesized RHAS was characterized by AAS, BET, DSC, FTIR, and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The RHS-NR compound also showed lower abrasion loss compared to the CS-NR compound, thus indicating better reinforcing efficiency of the RHS-filled NR compound. This result is in agreement with the results in a similar study by Lemessa Jembere and Fanta (2017). The authors also suggested that the surface area of the filler is one of the crucial aspects indicating the tensile strength of the composites, which would also increase the modulus of the compound.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…The RHS-NR compound also showed lower abrasion loss compared to the CS-NR compound, thus indicating better reinforcing efficiency of the RHS-filled NR compound. This result is in agreement with the results in a similar study by Lemessa Jembere and Fanta (2017). The authors also suggested that the surface area of the filler is one of the crucial aspects indicating the tensile strength of the composites, which would also increase the modulus of the compound.…”
Section: Introductionsupporting
confidence: 92%
“…As shown by Dominic et al (2013) and Lemessa et al (2017), a filler's high surface area could provide better interactions between the fillers and the rubber matrix. Consequently, the overall strength-related properties of the rubber compounds are improved.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Peak at 1375 cm -1 and 1432 cm -1 are characteristic of CH 2 deformation and at the region 2852-2925 cm -1 represented the CH 2 symmetric stretching vibrations [21][22]. All of NR composites filled SiO 2 show a strong peak at 464 and 1086 cm -1 that were attributed to the asymmetric bending vibration and the asymmetrical stretching vibration of Si-O-Si, respectively [23][24]. The region between 908-1259 cm -1 of pure NR was intercepted by the asymmetrical stretching vibration of Si-O-Si in NR composites.…”
Section: Ftir Spectral Analysismentioning
confidence: 97%